REPORT OF THE GRAVITY MEASUREMENT BY THE JAPANESE ANTARCTIC RESEARCH EXPEDITION, 1959-60 - Hiromiti SUZUKI; Shin-ichi OHASHI; Seiichi KAKINUMA (National Institute of Polar Research, 1961)
Gravity value at Astronomical point, Syowa station, was determined by observations with a WORDEN gravimeter in the third Japanese Antarctic Research Expedition 1958-59, and the following result has been obtained: g_=982.540cm/sec^2 Latitude 69°00'4S Longitude 39 35.4E Height 29.2m relative to g_=979.6470cm/sec^2. The accuracy of this value was estimated to be a few milligals by investigating the drift of the gravimeter during the period of the expedition and considering the uncertainty in the scale value of the gravimeter. This estimation was, however, based on several assumptions and the result may include a serious error. Fortunately, Syowa Station has been built on the ground and not on ice, therefore, we can reoccupy the very point of the station with our gravimeter and confirm the observed result. In the fourth expedition 1959-60, a re-measurement of the gravity value at Syowa Station was planned and carried out by using the same gravimeter in the way similar to the preceding expedition. It was confirmed that the gravimeter had a small and linear drift during the whole period of the expedition by continuous observations in Tokyo, Singapore, Cape Town as well as at Syowa Station. The drift rate for the period of 77 days during the forward and backward voyage between Cape Town and Antarctica was deduced to be +0.24 milligal per day. This value agreed well with a value, +0.25 milligal per day, which was deduced for the period of stay at Syowa Station. We have obtained a mean value of gravity, 982.5427, from observations at the station in this expedition. This is 2.6 milligal higher than the former mean value. Errors due to the drift and the changing in the scale value might have caused this difference. It is considered, however, that this is accurate enough to be used safely as a reference value in gravity measurement in this district. Therefore, we have concluded that the former value has an expected, accuracy and it is unnecessary to correct it by present result. On the way to and from Antarctica, ...